Colonial to global: Malaysian women's writing in English, 1940s-1990s - Abdul Manaf, Nor Faridah; Muhammad, A. Quayum (Research Centre,IIUM, 2003)
This book looks at various literary works written by Malaysian women ranging from the pre-independence period up till the 1990s.